“Technology acceptance model among employees in Jabatan Kerja Raya Malaysia” / Nadiah Hashim - Hashim, Nadiah (Faculty of Business and Management, 2010)
The Technology Acceptance Model (TAM) represents an important theoretical contribution toward understanding Information System (IS) usage and Information System (IS) acceptance behaviors. TAM was developed by Davis to explain computer usage behavior. The goal of TAM is to provide an explanation of the determinants of computer acceptance that is general, capable of explaining user behavior across a broad range of end-user computing technologies and user populations. TAM uses Theory of Reasoned Action (TRA) as a theoretical basis for specifying causal linkages which is Perceived Ease of Use (PEOU), Perceived Usefulness (PU) and Attitude toward Using (A). PEOU refers to the degree to which the user expects the target system to be free of effort. PU is defined as the user’s subjective probability that using a specific application system will increase his or her job performance within an organizational context. Both PEOU and PU predict attitude toward using the system, defined as the user’s desirability of his or her using the system. According to the employees’ views, the findings are as follows: (1) there is a relationship between perceived ease of use and attitude toward using the system, (2) there is a relationship between perceived usefulness and attitude toward using the system. The findings give a better understanding about level of attitude toward using the technology among employees in Jabatan Kerja Raya Melaka.